2012
DOI: 10.14429/dsj.62.1340
|View full text |Cite
|
Sign up to set email alerts
|

Hypersonic Intake Starting Characteristics–A CFD Validation Study

Abstract: Numerical simulation of hypersonic intake starting characteristics is presented. Three dimensional RANS equations are solved alongwith SST turbulence model using commercial computational fluid dynamics (CFD) software. Wall pressure distribution and intake performance parameters are found to match well with experimental data for different free stream Mach number in the range of 3-8. The unstarting of the intake is traced from the sudden drop of mass capture ratio. Wall condition (adiabatic or isothermal) is see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 20 publications
4
14
0
Order By: Relevance
“…The computed performances in terms of mass capture and total pressure recovery for the different cases reported in Table 4, are in agreement with experimental and numerical results for similar air intakes available in the literature [25]. Furthermore, the very limited deterioration of the inlet performances due to the asymmetry of the shock structures, ensures a stable combustion during the hypersonic cruise.…”
Section: Turbo-ramjet Inlet Designsupporting
confidence: 85%
“…The computed performances in terms of mass capture and total pressure recovery for the different cases reported in Table 4, are in agreement with experimental and numerical results for similar air intakes available in the literature [25]. Furthermore, the very limited deterioration of the inlet performances due to the asymmetry of the shock structures, ensures a stable combustion during the hypersonic cruise.…”
Section: Turbo-ramjet Inlet Designsupporting
confidence: 85%
“…Mousavi et al 19 successfully predicted the position and the shape of the shock train in a convergent-divergent nozzle. The employment of the shear stress transport model (SST) allowed Saha et al 20 to achieve a good agreement between the predicted and measured wall pressure in an intake with freestream Mach number from 3 to 8. Zhang et al 21 found the SST model suitable to solve the flow field in isolators with adverse pressure gradients caused by the combustion heat release.…”
Section: Introductionmentioning
confidence: 99%
“…However, computations which include the interaction between shock waves and turbulence are highly sensitive to the turbulence closure model. 8,16 The shear stress transport model (SST) was successfully used by Saha et al 17 to predict the wall pressure in an intake with freestream Mach number from 3 to 8, but the numerical simulation performed by Gawehn 18 strongly deviated from the experimental findings. By using the Additionally, research on high-speed isolators has mainly focused on cylindrical ducts, and only recently on rectangular cross-sections.…”
Section: Introductionmentioning
confidence: 99%